2014
DOI: 10.1080/13698575.2014.942258
|View full text |Cite
|
Sign up to set email alerts
|

The mutual constitution of risk and inequalities: intersectional risk theory

Abstract: This article examines the conceptual importance of integrating risk and intersectionality theory for the study of how risk and various forms of inequality intersect and are mutually constitutive. We argue that an intersectional perspective can advance risk research by incorporating more effectively the role of such social categories as gender and race into the analysis of 'risk' as an empirical phenomenon. In doing so, it articulates more clearly the connection between the social construction of risk with, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 59 publications
0
53
0
4
Order By: Relevance
“…comprehending the intersectionality of structures of class, gender, ethnicity, age and so on offer important purchase on this 'exercise of power' (Olofsson et al, 2014). The value of such insights is usefully illustrated through these authors' reflections on recent tendencies in welfare policy, but also in the following article by Montelius and Giritli-Nygren.…”
Section: Contrasting Rationalities and The Legitimacy Of Risks And Pomentioning
confidence: 98%
“…comprehending the intersectionality of structures of class, gender, ethnicity, age and so on offer important purchase on this 'exercise of power' (Olofsson et al, 2014). The value of such insights is usefully illustrated through these authors' reflections on recent tendencies in welfare policy, but also in the following article by Montelius and Giritli-Nygren.…”
Section: Contrasting Rationalities and The Legitimacy Of Risks And Pomentioning
confidence: 98%
“…Los desafíos de la incorporación de los presupuestos conceptuales y metodológicos y la potencialidad de la interseccionalidad para el campo de las investigaciones constituyen el foco del eje temático denominado debates teórico-metodológicos de la interseccionalidad en la salud, que incluye diez trabajos (16,17,19,20,21,22,23,24,25,26) producidos en los últimos diez años, cinco de los cuales corresponden a autoras canadienses. Autoras como Olena Hankivsky y Lisa Bowleg, originalmente vinculadas a los women's studies, promueven "revisiones críticas" a partir de sus áreas de actuación (estudios canadienses de los determinantes sociales de la salud y estudios estadounidenses sobre raza y minorías en salud, respectivamente), quienes enumeran y proponen debatir críticamente las posibles contribuciones del abordaje de la interseccionalidad como herramienta teórico-metodológica para comprender mejor y enfrentar las diferenciaciones y desigualdades en salud, hecho que actualmente también se coloca como desafío global (17,18,19) .…”
Section: Los Debates Teórico-metodológicos En Interseccionalidad Y Saludunclassified
“…To summarize, research has shown that lived experience, including exposure or vulnerability to risk, can influence risk perception (for instance, Konheim, ; Olofsson et al, ). This view of risk perception corresponds to the section about organizations above, which argues that vulnerability and privilege can affect risk perception—because different roles within an organization have varying amounts of perceived and real power, control, vulnerability, and exposure to risk.…”
Section: A Model For the Social Construction Of Risk In Digital Presementioning
confidence: 99%